2011
DOI: 10.5336/medsci.2009-16017
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Melatonin on the Retinas of Rats with Streptozotocin-Induced Diabetes Mellitus

Abstract: A AB BS S T TR RA AC CT T O Ob b j je ec c t ti i v ve e: : To in ves ti ga te the pro tec ti ve ef fect of me la to nin on the re ti nas of rats with strep to zo to cin (STZ)-in du ced di a be tes mel li tus (DM). M Ma a t te e r ri i a al l a an nd d M Me et t h ho od ds s: : Thre e gro ups of seven ma le Wis tar rats we re en rol led in this study: (1) a di a be tic gro up, (2) a di a be tic gro up tre a ted with me la to nin, and (3) con trol gro up. Di a be tes was in du ced with a sing le do se of 60 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
1
0
0
1
Order By: Relevance
“…In another study, it was demonstrated that i.p. injection of MEL (10 mg/kg/day) for 30 days to diabetic rats reduced the MDA concentrations in retina . These data and results of the present study clearly show that MEL causes retinoprotection and this might be through reduction in oxidative stress parameters and by its antioxidant properties.…”
Section: Discussionsupporting
confidence: 81%
“…In another study, it was demonstrated that i.p. injection of MEL (10 mg/kg/day) for 30 days to diabetic rats reduced the MDA concentrations in retina . These data and results of the present study clearly show that MEL causes retinoprotection and this might be through reduction in oxidative stress parameters and by its antioxidant properties.…”
Section: Discussionsupporting
confidence: 81%
“…Streptozotosin ve alloksan ile oluşturulan deneysel diabette melatonin uygulamasının pankreasta koruyucu etkisi olduğu gösterilmiştir [24]. Streptozotosine bağ-lı diabet modelinde melatonin uygulaması serbest radikal düzeyini azaltmış ve NO düzeyindeki artışı radikal temizleyici özelliği ile önlemiştir [25], benzer bir çalışmada farelerin retinalarında ki MDA değişi-mi incelenmiş ve melatoninin MDA düzeyini azaltıcı etkisi gösterilmiştir [26]. Yaşlanma sürecinde artan oksidatif stres ve NO düzeyi inflamasyona zemin hazırlayarak pankreas dokusunda yaşa bağlı olarak glukoz toleransının azalması ve diyabete yatkınlığa neden olabilir.…”
Section: Discussionunclassified